Eye movements of second language learners when reading spaced and unspaced Chinese texts - Cui, Yaqiong (Frontiers in Psychology, 2023)
Unlike English, Chinese does not have interword spacing in written texts, which poses difficulties for Chinese-as-a-second-language (CSL) learners’ identification of word boundaries and affects their reading comprehension and vocabulary acquisition. The eye-movement literature has suggested that interword spacing is important in alphabetic languages; examining languages that lack interword spaces such as Chinese, thus, may help to inform theoretical accounts of eye-movement control and word identification during reading. Research investigating the interword spacing effect in reading Chinese showed that adding spacing facilitated CSL learners’ reading comprehension and speed (Bassetti, 2009; Yao, 2011), as well as vocabulary learning (Bai et al., 2013). However, the bulk of this research mainly looked at the learning outcomes (off-line measures), with few studies focusing on L2 learners’ reading processes. Building on this background, this study seeks to provide a descriptive perspective of the eye movements of CSL learners. In this study, 24 CSL learners with intermediate Chinese proficiency were recruited as the experimental group, and 20 Chinese native speakers were recruited as the treatment group. The EyeLink 1000 eye tracker was used to record their reading of four segmentation conditions of Chinese texts, namely, no space condition, word-spaced condition, non-word-spaced condition, and pinyin-spaced condition. Results show that: (1) CSL learners with intermediate Chinese proficiency generally spent less time reading Chinese texts with spaces between words, and they showed more gazes and regressions when reading texts without spaces; (2) Non-word-spaced texts and Pinyin-spaced texts interfere with CSL learners’ reading process; and (3) Intermediate CSL learners show consistent eye movement patterns in the normal no-space condition and word-spaced condition. We conclude that word boundary information can effectively guide CSL learners’ eye movement behaviors and eye saccade planning, thus improving reading efficiency.